Islamic Psychology Interventions for Enhancing Student Resilience and Mental Well-being in Modern Educational Settings - Ahmed Al-Mansoori; Mariam Al-Jassim; Harizahayu Harizahayu (Islamic Studies in the World, 2025)
This study examines the role of Islamic psychology interventions in strengthening student resilience and mental well-being in contemporary educational settings. Growing concerns about rising stress, anxiety, and emotional instability among students highlight the need for culturally grounded and spiritually informed mental health support. Islamic psychology, with its integrative view of the human soul (nafs), cognition, emotion, and spiritual consciousness, offers a holistic framework that complements modern psychological approaches. Concepts such as tawakkul (trust in God), sabr (patience), dzikr (mindfulness of God), and emotional self-regulation rooted in prophetic tradition provide alternative pathways for promoting resilience and well-being. The study aims to identify effective Islamic psychology-based interventions and evaluate their relevance and applicability within modern school contexts. A qualitative design was used, involving document analysis of classical and contemporary Islamic psychology literature, thematic analysis of intervention models, and semi-structured interviews with Islamic psychologists, school counsellors, and educators. The multi-source data allow for an in-depth exploration of both theoretical foundations and practical school-based applications. The findings indicate that Islamic psychological interventions enhance resilience through three primary mechanisms: strengthening spiritual coping strategies, cultivating emotional regulation through reflective practices, and reinforcing positive self-concept grounded in divine purpose. Schools implementing these approaches report improvements in students’ stress management, interpersonal relationships, and overall emotional well-being. The study concludes that integrating Islamic psychology into school-based mental health programs provides a culturally responsive and spiritually enriching alternative for student support. The findings highlight the potential of Islamic psychological principles to bridge faith-based values and contemporary mental health needs in diverse educational environments.